PEMBANTAIAN RAYMOND PIERRE PAUL WESTERLING DI SULAWESI SELATAN SEBAGAI UPAYA BELANDA MENDIRIKAN NEGARA INDONESIA TIMUR (1946-1947) - Rafi Zain Yusuf; Ridwan Melay; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The new Indonesia gained independence should return to face the Netherlands who want to re-colonize Indonesia. NICA coming to Indonesia is trying to arm the Royal Nerderlands Indisch Leger (KNIL), the Dutch royal army to Indonesia, with the aim of provocation and terror against the people of Indonesia. In addition to the military, the Netherlands is also planning to create a form of federation in Indonesia that aims to weaken the Republic of Indonesia one of which is the State of East Indonesia. But the Dutch effort to establish the State of East Indonesia should be blocked, because the situation in South Sulawesi were not safe it is caused by the people's resistance against the Dutch and Allied soldiers who refused the Dutch presence in South Sulawesi. The purpose of this study were (1) to know who Raymond Westerling, (2) to know the background of the Dutch established the State of East Indonesia, (3) to determine the people's resistance against the Dutch in South Sulawesi, (4) to determine the Dutch strategy in the face popular resistance in South Sulawesi, (5) to determine the role of slaughter Westerling of the establishment of the State of East Indonesia, (6) to find out the Dutch and Indonesian government action against the slaughter Westerling, (7) to determine the end of the State of East Indonesia. The method used is the method Historically, the data collected through technical literature and technical documentation. In analyzing the data is used dekriftif qualitative. Results from this study is that the Federal State of East Indonesia can stand, then the Netherlands need to create a safe state in South Sulawesi. To achieve this goal, then sent troops Westerling and Depot Speciale Troepen to quell popular resistance, and how that is done by Westerling is to carry out the slaughter/killing people in South Sulawesi. Westerling massacres and DST troops in South Sulawesi can extinguish the resistance of the people that made the Netherlands could be immediately set up the State of East Indonesia is the administrative center of MakassarKey Words: Westerling, DST, NIT.